Hydrological Assessment and Water Quality Characteristics of Chini Lake, Pahang, Malaysia - Islam, Mir Sujaul; B. S., Ismail; Muhammad Barzani, Gasim; A. R., Sahibin; T., Mohd Ekhwan (International Digital Organization for Scientific Information (IDOSI), 2012)
The purpose of this study was to assess the hydrological properties and water quality characteristics of Chini Lake in Pahang, Malaysia. A total of seven sampling stations were established at the main Feeder Rivers of Chini Lake for measurement of stream flow. A total of 10 monitoring stations covering the study area were selected for water sampling. Fourteen water quality parameters were analyzed based on in-situ and ex-situ analysis for two seasons and laboratory analyses were carried out according to the HACH and APHA methods.Stream flow from the seven Feeder Rivers into the Chini Lake was relatively slow, ranging from 0.001 to 1.31 m /s3 or an average of 0.21 m3 /s. According to the INWQS (Interim National Water Quality Standards, Malaysia) classification, the temperature was within the normal ranges; conductivity, total suspended solids (TSS), nitrate, sulphate and total dissolved solids (TDS) were categorized under class I, while turbidity, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), ammoniacal nitrogen and phosphate came under class II and pH under class III. Furthermore water quality in Chini Lake varied temporally and spatially and the most affected parameters were pH, TSS, turbidity, DO, ammoniacal nitrogen, phosphate and conductivity. Based on the Malaysian Water Quality Index (WQI), the water in the Chini Lake was classified under class II, meaning it is suitable for recreational activities and safe for body contact.